Sustainability Disclosure, Capital Structure, and Firm Value: The Moderating Role of Operational Activities - Loxyanto, Feby; Kurniawati, Lintang (Sean Institute, 2026)
In the era of globalization, increasing firm value is crucial for attracting investors and maintaining competitiveness. However, prior research regarding the determinants of firm value remains inconsistent. This study aims to analyze the influence of sustainability report disclosure and capital structure on firm value, while examining the moderating role of operational activity. The research employs a quantitative approach using secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2023 period. Samples were selected using purposive sampling, and data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that sustainability report disclosure has a significant positive effect on firm value, reflecting that transparency enhances investor confidence. Conversely, capital structure has a significant negative effect, suggesting that high debt levels may increase financial risk and lower firm value. Furthermore, operational activity proves to be a significant moderating variable. Specifically, high operational activity weakens the influence of both sustainability reporting and capital structure on firm value. This implies that when companies demonstrate high operational efficiency and asset utilization, investors tend to prioritize actual operational performance over sustainability disclosures or funding decisions when assessing firm value. These findings contribute to the literature by highlighting how internal operational efficiency shifts investor focus and alters the impact of financial and non-financial disclosures.